Investigação de Chlamydia psittaci em aves de estimação da cidade de Uberlândia - Borges, Andressa Afonso (2018)
Chlamydiosis is a public health important zoonosis, and its transmission to humans occurs mainly through contact with pet birds. These animals rank the second position in most popular pets in Brazil, where the occurrence of chlamydiosis is underestimated, although studies indicate that the disease is endemic in the country. Therefore, the present work aimed to investigate the occurrence of Chlamydia psittaci in 68 cockatiel chicks (Nymphicus hollandicus) of the city of Uberlandia, Minas Gerais, Brazil. Samples of choana, cloaca, and fresh fecal samples were collected for the detection of the bacteria by PCR test. The occurrence found was null. This work concludes that it is important to raise the awareness of owners and breeders about measures to prevent and control this disease, and that orientating them about the risks of overusing antibiotics is a public health issue.